Plan estratégico de marketing para la Clínica Nataly de la ciudad de Loja periodo 2011-2016 - Balbuca Castillo, Ángel Bolívar (2015)
The present investigation work has been carried out in the Clinical Nataly of the City of Loja, where he/she has been able to observe some falencias, the same ones that have been detailed and have more than enough its base, they think about proposals, alternative of solution. The topic of the present work is "STRATEGIC PLAN DE MARKETING FOR THE CLINICAL NATALY OF THE CITY DE LOJA PERIOD 2011 - 2016" where was carried out an analysis, on its weaknesses and strengths, opportunities and threats, which allowed to establish some solution alternatives. For the development of this work he/she left of the outlined objectives: General objective: "To elaborate a strategic plan of marketing for the Clinic "Nataly" of the city of Loja. The specific objectives were: To carry out a market study, to Make an analysis of the internal and external atmosphere, to Execute an analysis FODA, to outline objectives, goals, and political, to Elaborate a strategic plan of marketing for the Clinic "Nataly" of the city of Loja. The different methods were used and technical of investigation that helped to elaborate the strategic plan of marketing. The used methods were: scientific, analytic, historical, inductive, deductive, statistical and as technical of investigation: observation, interviews, it interviews, bibliographical summary that you/they helped to elaborate the strategic plan. In the results he/she took in consideration the obtained results of the interview applied the proprietor of the Clinical Nataly, as well as the surveys applied the employees and clients of the company, information that allowed to know how he/she is the company at the present time. In the present thesis he/she was carried out an application from an interview to the gentleman manager, the observation to the institution and their environment, the application of 232 surveys to the clients; and the application of 25 surveys to all the employees of the Clinical Nataly; all this helps to elaborate the "Strategic Plan of Marketing of the Clinical Nataly", the same one that will be suggested to the manager and directive of the institution for their application and setting in march. In the external analysis it was analyzed the economic, political factors - legal, social, technological, competitive, jointly with the five Forces of Porter, the pondered total obtained through the elaboration of the main EFE (2.57), it allowed to determine that the Clinic has a high grade of opportunities that guarantees him to be able to continue ahead and to be developed in a positive way in the means. In the internal analysis it was determined that the pondered total obtained through the elaboration of the main EFI is (2.02), therefore the Clinic has a high grade of strengths and a strong internal position that it guarantees him to be able to continue ahead and to be developed in a positive way its contour. In the analysis of the main FODA, In the external factors, the opportunities are: Political stability of the Ecuador, excellent International relationships, Improvement of the levels of life and of revenues of the Ecuadorians, economic Growth of the Ecuador, technological Advance of the country, Minimum power of the suppliers' negotiation, Lack of opportune attention to the patient for the government's sector health; he/she settled down Threats: Laws that foment the benefit and gratuitousness of medical services on the part of the State, Invigoration of the public services of health of the country, permanent Improvement of the quality and covering of the services of public health in the country, fiscal Politicians that attempts to the clinic, disloyal Competition, I Increase of new competitors, Wide rivalry among the competitors current, High power of the clients' negotiation, Existence of services substitutes, For the unemployment level in the County of Loja, doesn't have necessary revenues for the medical care. For the unemployment level in the County of Loja, it doesn't have necessary revenues for the attention it not prescribes Competition controlled by the Organisms of Control, growing Entrance of products substitutes, Matter prevails for the jam it comes from the public net, for what the access to sources of water is not indispensable, permissible Market to the entrance of new competitors, Unemployment, political Uncertainty. Proceeding then to carry out the Main EFE, where the result pondered total of 2.67 was obtained. In the same way he/she is carried out the internal analysis that allowed to build the Strengths: Permanency like Client, Excellent facilities physical, Excellent quality of attention to the public, Excellent technological system, Variety of specialties medical, Excellent image corporate, Excellent location physical, Excellent climate labor, Pleasant work atmosphere, Solid economic solvency, Professional Experience, Possesses mission and managerial vision, Own Building You proceeds to structure the Main EFI, which had as a result in the pondered total 2.02 what means that the Distribuidora Dilutes Breeze, if he/she has internal problems that require to be assisted, for that which you/they will think about strategies that allow to eliminate the existent weaknesses. With these considerations and by means of the Womb of High Impact they thought about four strategic objectives: To impel the development and corporate growth of the Clinical Nataly through strategic alliances with different local organizations, to Promote the services that the Clinical Nataly lends in the different media. To implement incentives and credit offers for our clients, to Elaborate a plan of Training for the whole Human Talent of the Clinic. Also determining that the total cost of the STRATEGIC PLAN DE MARKETING, is of $ 25,132.50. In the work they settle down finally finally those the conclusions and recommendations that have felt pertinent.